Study on Applicability of V500 High-speed Pantograph Models - ZHONG Wei-guang; ZHANG Wei-hua; MEI Gui-ming (机车电传动)
To analyze applicability of pantograph models, dynamic parameter identifying was implemented for domestic independentdevelopedV500 high-speed pantograph prototype, and pantograph two-lumped-mass model and three-lumped-mass model kinetic parameterwere obtained. Pantograph multiple-rigid-body model, rigid-flexible hybrid-body model, two-lumped-mass model and three-lumped-massmodel were built, frequency response of which was analyzed. Pantograph-catenary dynamic system was established based on Wuhan-Guangzhou line, and the pantograph models applicability was analyzed by dynamic simulation. The results showed that: a rigid-body modelcould be replaced by a two lumped-mass model, and a rigid-flexible hybrid-body model could be replaced by a three-lumped-mass model; twolumped-mass model had better applicability under 250 km/h speed, and on contrast, three-lumped-mass model had better applicability above250 km/h speed.